Bloom taxonomy revisited: analysis from western and Islamic perspectives - Abdullah, Norillah (2014)
Bloom taxonomy has been the basis of education structure in learning method and assessment. Underpinning the behavioral objectives, Bloom Taxonomy informs the change of knowledge, attitude and skills which assist teachers to transform learning from low to high order thinking (HOT). Unfortunately, Bloom taxonomy has encountered a shortcoming of the assumption of men as merely the body and mind without addressing the spiritual entity. For Muslims to adapt purely on Bloom taxonomy in planning and learning process reflects the ignorance of the fitrah or primordial of men which is the most crucial aspect in Islam. Therefore this taxonomy has to be revisited from the perspective of Muslim model of thinking. Further educational objectives in cognitive domain should be explored. This research aims at highlighting the assumption of metaphysical foundation of Bloom Taxonomy which is contradicting with the Islamic metaphysic. It also attempts to discover the differences between Bloom and taxonomy of thinking process which resulted from different metaphysical foundations and it’s implication to the Muslim educational setting. The methodology of this research is based on the philosophical analysis and historical development of Bloom taxonomy and Malik Badri in order to identify the main differences between their taxonomies of the thinking process.